PERAN PENDIDIKAN NILAI DALAM PEMBENTUKAN KEPRIBADIAN PESERTA DIDIK - Francius Simanullang, Reno; Daulat Saragi; Yacobus Ndona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In order to eliminate the hubris that frequently arises, value education helps students comprehend, absorb, and make the appropriate decisions in a variety of personal, family, community, and state challenges. The value inculcation strategy places a strong emphasis on forming pupils' character through the instillation of societal ideals. Character education taught by teachers emphasizes the importance of morality, good attitudes, and actions in children. The people of Indonesia now require character education that upholds Pancasila ideals, specifically the qualities of piety, honesty, compassion, ethics, and civility. Students' opinions on a variety of topics and from a variety of angles are shaped by character education. Here, Pancasila education plays a key role in promoting the virtues of model behavior in being polite and courteous by strengthening students' religious inclinations, offering guidance, and instructing elementary school pupils in obedience, following social norms, respecting democracy, the nation, and the environment, among other things. Observations and interviews are used in this descriptive-social study design. As a result, information about the community's environmental circumstances and common issues faced by parents and individuals who are impacted is discovered.